2014
DOI: 10.1007/s40279-014-0179-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Workloads, Physical Performance, Injury and Illness in Adolescent Male Football Players

Abstract: The combined capacity for adolescent males to grow, train and improve physical performance highlights and underscores an exciting responsiveness to training in the football environment. However, the capacity to train has some established barriers for adolescents experiencing high workloads, which could also result in negative consequences. Additional research on stage-appropriate training for adolescent male footballers is required in order to address the knowledge gaps and enhance safe and efficient training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 67 publications
1
112
1
1
Order By: Relevance
“…As such, it is important that each player is treated individually such that training responses are considered in the context of previous, current and future loading. [1][2][3][4] Another consideration for the inconsistency in RPE reporting might be factors associated with team characteristics. Indeed, Gallo et al that RPE load is influenced by position, playing experience and time-trial performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is important that each player is treated individually such that training responses are considered in the context of previous, current and future loading. [1][2][3][4] Another consideration for the inconsistency in RPE reporting might be factors associated with team characteristics. Indeed, Gallo et al that RPE load is influenced by position, playing experience and time-trial performance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a growing body of literature shows that the management of training load is effective in reducing the risk to injury [1][2][3] as well as improving athletic performance. 4 A variety of training load monitoring tools can be used to measure the perceived load of an athlete to training. 5 One such popular approach in the sports domain consists of subjectively asking the athlete to rate their perceived exertion (RPE) for a given session.…”
Section: Introductionmentioning
confidence: 99%
“…Training-related changes have been evident in adolescent athletes after a range of training modalities (e.g., strength, smallsided games, sport-specific training; Ref. 15), and therefore a combination of the processes of growth and maturation alongside training interventions would result in annual improvements in anthropometric and physical characteristics. Although most characteristics improved across time, there was no significant annual change in sum of 4 skinfolds or 10-m or 20-m sprint performance, which is also, consistent with previous research (9,34).…”
Section: Discussionmentioning
confidence: 99%
“…To provide an overall comparison between elite youth and professional adult soccer players, a more detailed classification focused on the intensity of training is needed. In addition, youth soccer players are clearly not as physically mature as professional adult soccer players, 41 and researchers 5,51 have suggested that increased exposure to training may be linked to higher injury incidences. Hence, observing stress and recovery in youth soccer players may enable the identification of athletes who are at risk for injuries and illnesses.…”
Section: Influence Of Certain Variables On Youth Soccer Playersmentioning
confidence: 99%